VD_FINDINFO Faillite / 2020 / 3 vom 20. Januar 2020 - VD Tribunal cantonal (2020)
PROCÉDURE DE FAILLITE, MOTIVATION DE LA DEMANDE, DÉCISION D'IRRECEVABILITÉ | 174 al. 1 LP, 174 al. 2 LP, 321 al. 1 CPC (CH)